Volodymyr Garriyovych Klimovitsky - Donetsk Research Institute of Traumatology and Orthopaedics of Gorky DNMU, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article deals with the 60th birthday of V.G. Klimovitsky: Doctor of Medical Science, Professor, winner of the State Prize of Ukraine in Science and Engineering, Honoured Doctor of Ukraine, Director of the Research Institute of Traumatology and Orthopaedics, Head of the Department of Traumatology, Orthopaedics and Surgery in Extreme Situations of Donetsk National Medical University of Maxim Gorky, Chief Physician of the Donetsk Regional Traumatological Hospital.